Autonomia e integração regional no contexto do Mercosul. Uma análise considerando a posição do Brasil - Vigevani, Tullo [UNESP]; Ramanzini, Haroldo (My University, 2010)
This paper aims to examine regional integration processes in South America, particularly in Mercosur. The point of departure is the study of Brazilian foreign policy in the region. Possible consequences of international changes will be discussed, as well as the significance of new social and political forces. Continuity and ruptures in Brazilian behaviour as regards integration will be identified to understand strengths and weaknesses in building an independent position and in search of balance among other international power centres.

El objetivo de este trabajo es analizar los procesos de integración regional en América del Sur, particularmente del Mercosur, partiendo para eso del análisis de la política externa brasilera para la región. Discutiremos las posibles consecuencias de los cambios internacionales, además del significado de la emergencia de nuevas fuerzas políticas y sociales. Se verificarán continuidades y transformaciones en el comportamiento de Brasil en relación a la integración, en la búsqueda de los puntos fuertes y débiles en la construcción de una posición autónoma y que revista mayorequilibrio frente a los demás centros internacionales de poder.
Keywords: América do Sul; Argentina; Mercosul; Política exterior do Brasil; Integração regional